2015
DOI: 10.1002/2014pa002752
|View full text |Cite
|
Sign up to set email alerts
|

Growth of the Maritime Continent and its possible contribution to recurring Ice Ages

Abstract: The areal extent of the Maritime Continent (the islands of Indonesia and surrounding region) has grown larger by~60% since 5 Ma. We argue that this growth might have altered global climate in two ways that would have contributed to making recurring Ice Ages possible. First, because rainfall over the islands of the Maritime Continent not only is heavier than that over the adjacent ocean but also correlates with the strength of the Walker Circulation, the growth of the Maritime Continent since 5 Ma may have cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 274 publications
(515 reference statements)
4
71
0
1
Order By: Relevance
“…Thus, results from our analysis could reveal that folding related to crustal shortening has occurred in the recent past (b 5 Ma) and could still be prevalent in the onshore fold and thrust belts of the Rajang Group Interior Highlands of Sarawak. Recent studies have confirmed that most of the high terrains in the islands of Southeast Asia are young (b 10 Ma) and mountain ranges have grown in the past 5 Ma (Molnar and Cronin, 2015), further confirming the results obtained by us.…”
Section: Effects Of Crustal Shorteningsupporting
confidence: 88%
“…Thus, results from our analysis could reveal that folding related to crustal shortening has occurred in the recent past (b 5 Ma) and could still be prevalent in the onshore fold and thrust belts of the Rajang Group Interior Highlands of Sarawak. Recent studies have confirmed that most of the high terrains in the islands of Southeast Asia are young (b 10 Ma) and mountain ranges have grown in the past 5 Ma (Molnar and Cronin, 2015), further confirming the results obtained by us.…”
Section: Effects Of Crustal Shorteningsupporting
confidence: 88%
“…The constriction of the Indonesian Seaway with the related emergence of the Maritime Continent with a gain in landmasses of ~60% including many islands contributed to the general global cooling trend since ~5 Ma45. Intensified weathering of basaltic rocks along with the rising of the Maritime Continent might have contributed to a long-term CO 2 drawdown45.…”
Section: Resultsmentioning
confidence: 99%
“…Intensified weathering of basaltic rocks along with the rising of the Maritime Continent might have contributed to a long-term CO 2 drawdown45. Further, the slight tectonic-induced decrease of eastern tropical Pacific SST might have led to a stronger east-west Pacific SST gradient causing a stronger Walker circulation with far reaching climatic effects on North America45. The tectonic-induced distinct freshening of the subsurface eastern tropical Indian Ocean due to the restriction of the Indonesian Throughflow waters during ~3.5–2.95 Ma1315 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, basaltic catchments weather faster than other silicates and account for approximately 20-35% of the modern global silicate weathering and CO2 consumption flux, while occupying less than 5% of sub-aerial continental area (Gíslason et al, 1996(Gíslason et al, , 2009 have been critically important in controlling past levels of atmospheric CO2 (pCO2) (Li and Elderfield, 2013;Kent and Muttoni, 2013;Molnar and Cronin, 2015;Jagoutz et al, 2016). However, scaling modern observations of weathering fluxes from catchments to both large spatial and temporal scales (e.g., Wallmann, 2001;Lefebvre et al, 2013;Li and Elderfield, 2013;Kent andMuttoni, 2008, 2013;Mills et al, 2014a;Li et al, 2016;Jagoutz et al, 2016;Cox et al, 2016) remains a challenge due to the lack of phenomenological modeling frameworks that predict weathering fluxes at both catchment and global scales under different climate states.…”
Section: Introductionmentioning
confidence: 99%